2018
DOI: 10.11646/phytotaxa.344.3.2
|View full text |Cite
|
Sign up to set email alerts
|

Ophiocordyceps neonutans sp. nov., a new neotropical species from O. nutans complex (Ophiocordycipitaceae, Ascomycota)

Abstract: Ophiocordyceps nutans is an entomogenous fungus growing on true bugs (Hemiptera), which has a presumed worldwide distribution. During forays of entomogenous fungi in Brazil, specimens morphologically similar to O. nutans were collected from the Atlantic Forest and Cerrado domains of Neotropical region. Morphological comparisons, as well as molecular phylogenetic analyses using ITS, led us to conclude that the neotropical specimens represent a new species Ophiocordyceps neonutans. The Neotropical occurrence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 23 publications
2
1
0
Order By: Relevance
“…They infected the Proxys punctulatus; the Halyomorpha halys, the Acanthosoma labiduroides, the Acanthosoma labiduroides and the Clavigralla scutellaris. The similarity in findings have been observed in O. nutans from Japan [15], although O. neonutans is exclusively found in the Pentatomidae family [2] (Figure 3).…”
Section: Hostsupporting
confidence: 78%
See 1 more Smart Citation
“…They infected the Proxys punctulatus; the Halyomorpha halys, the Acanthosoma labiduroides, the Acanthosoma labiduroides and the Clavigralla scutellaris. The similarity in findings have been observed in O. nutans from Japan [15], although O. neonutans is exclusively found in the Pentatomidae family [2] (Figure 3).…”
Section: Hostsupporting
confidence: 78%
“…They infected the Proxys punctulatus; the Halyomorpha halys, the Acanthosoma labiduroides, the Acanthosoma labiduroides and the Clavigralla scutellaris. The similarity in findings have been observed in O. nutans from Japan[15], although O. neonutans is exclusively found in the Pentatomidae family[2] (Figure3).Among 65 collected specimens, O. nutans specimens have stinkbugs as the host insects, with 28 specimens being Halyomorpha halys, and there were 15 specimens were Lasianthus bidoupensis, corresponding to the frequencies of occurrence at 64,3%.Lasianthus bidoupensis (Rubiaceae), a new evergreen tree species, has been described and illustrated in Bidoup Nui Ba National Park, Lam Dong Province, southern Vietnam. Larger leaves and bracts, longer petioles, stipules, calyx and corolla tubes, and deep-red mature fruits distinguish this species.…”
supporting
confidence: 79%
“…It is a heterogeneous taxon comprising mainly insect pathogens. The stroma of Ophiocordyceps species remains attached to the corpses of the host, and the parasitized insects can be found in exposed environments such as, in the litter, underneath leaves, in stems, or even buried in the soil [ 14 , 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“… ovatospora ( Tang et al 2022 ). Other groups such as Ophiocordyceps nutans species complex attack stink bugs ( Friedrich et al 2018 ; Khao-ngam et al 2021 ) and Ophiocordyceps pseudoacicularis species complex were found occurring on Lepidoptera larvae ( Tasanathai et al 2020 ). These complexes have been proposed as distinct species, based on molecular phylogenetic studies and morphological characteristics.…”
Section: Discussionmentioning
confidence: 99%